OPTIMASI PEMBUATAN PERNIS DARI DAMAR - Erik Dahlian; Hartoyo Hartoyo; Erra Yusnita (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Varnish is a combined liquid of resin oil, solvent, pigment, drying agent, and additives. The additives in this regard are those when applied on wood's surface can form a dry layer which is harder and firmly stick to the surface.In a effort to enhance damar utilization, an investigation has been conducted on varnishmanufacturing of damar mata kucing of poor quality type. This investigation was intended to apply appropriate and more efficient methods of processing of varnish aimed at improving its quality and increasing commercial values aswell. Meanwhile, the target of this investigation was to get the varnishprocessing methods with low cost of investment which facilitate its application in the damar producing sites more economical.The results of this investigation revealed that the processing methods, implemented by adopting formula 66,0/24,0 k; 65.5/24,5 s and 65,5/24,5 k; were capable of producing varnish with satis factory quality which comply with the requirement of ICI 's paint factory. The use of low quality damar mata kucing mixed with particular solvent composed of toluene and kerosene can contribute to the operation of a smallscale industries economically more feasible.